Dually targeted bioinspired nanovesicle delays advanced prostate cancer tumour growth in vivo. (15th October 2021) - Ma, Guanglong; Severic, Maja; Barker, Matthew; Pereira, Sara; Ruiz, Amalia; Cheung, Calvin C.L.; Al-Jamal, Wafa T.
Abstract: Prostate cancer (PC) is second-leading cancer in men, with limited treatment options available for men with advanced and metastatic PC. Prostate-specific antigen (PSA) and prostate-specific membrane antigen (PSMA) have been exploited as therapeutic targets in PC due to their upregulation in the advanced stages of the disease. To date, several PSA- and PSMA-activatable prodrugs have been developed to reduce the systemic toxicity of existing chemotherapeutics. Bioinspired nanovesicles have been exploited in drug delivery, offering prolonged drug blood circulation and higher tumour accumulation. For the first time, this study describes the engineering of dually targeted PSA/PSMA nanovesicles for advanced PC. PSMA-targeted bioinspired hybrids were prepared by hydrating a lipid film with anti-PSMA-U937 cell membranes and DOX-PSA prodrug, followed by extrusion. The bioinspired hybrids were characterised using dynamic light scattering, transmission electron microscopy, Dot blot, flow cytometry and Western blot. Cellular binding and toxicity studies in PC cancer cell lines were carried out using flow cytometry, confocal microscopy, and resazurin assay. Finally, tumour targeting and therapeutic efficacy studies were performed in solid and metastatic C4-2B-tumor-bearing mice. Interestingly, our PSMA-targeted hybrids demonstrated high cell uptake in PSMA-expressing cells with significant accumulation in solid and metastatic C4-2B tumour tissues following intravenous administration. More promisingly, our dually targeted PSA/PSMA hybrid significantly slowed down the C4-2B tumour growth in vivo, compared to free DOX-PSA and non-targeted PSA-hybrid. Our PSA/PSMA bioinspired hybrid could offer a highly selective treatment for advanced PC with lower side effects. Statement of significance: This study investigates a new approach to treat prostate cancer using dually targeted bioinspired nanovesicle . Our bioinspired vesicles are made mainly of a human blood cell membrane with a ligand recognising a specific marker (PSMA) on the surface of the prostate cancer cells. The present work describes the successful loading of a doxorubicin prodrug linked to a PSA- activatable peptide into these targeted bioinspired nanovesicle, where the active PSA enzyme presents in these cells converts the drug to its active form. Our dually targeted PSA/PSMA hybrid vesicles has successfully improved site-specific prodrug delivery to tackle advanced prostate cancer, offering a novel and effective prostate cancer treatment. Graphical abstract: Image, graphical abstract